Human Claudin-7 cis-Interactions Are Not Crucial for Membrane-Membrane (Trans-) Interactions - Ahlswede, Lena; Siebenaller, Carmen; Junglas, Benedikt; Hellmann, Nadja; Schneider, Dirk (Frontiers in Molecular Biosciences, 2022)
Human Claudin-7 (Cldn7) is a member of the Claudin (Cldn) superfamily. In vivo, these proteins form tight junctions, which establish constricted connections between cells. Cldns oligomerize within the membrane plane (= cis-interaction), and also interact with Cldns from adjacent cells (= trans-interaction). Interactions of Cldns are typically studied in vivo and structural analyses of isolated Cldns are limited. Here, we describe heterologous expression in E. coli and purification of human Cldn7, enabling in vitro analyses of the isolated protein using detergent and model membrane systems. Cldn7 exists as a monomer, hexamer, and various higher oligomers in micelles. While only limited unfolding of the protein was observed in the presence of the anionic detergent sodium dodecyl sulfate, decreased ionic strength did affect Cldn7 cis-interactions. Furthermore, we identified two amino acids which mediate electrostatic cis-interactions and analyzed the impact of disturbed cis-interaction on trans-contacts via atomic force microscopy and monitoring Förster resonance energy transfer between fluorescently labeled Cldn7-containing proteoliposomes. Our results indicate that Cldn7 cis-oligomerization might not be a prerequisite for establishing trans-contacts.